Prevalence of Premalignant Conditions and Their Transformation Into Oral Cancers: A Clinical Study - Batchu Pavan Kumar; Pallavi Narra; Vuyyuru Vidya Devi; Vishnu Gowtham Marella; Saudamini G. More; Sheetal Mujoo; Neshaneni Satish Kumar (Wolters Kluwer Medknow Publications, 2024)
Objectives: The purpose of this study is to look at how often premalignant oral diseases are among patients who visit a tertiary care center, as well as how often these problems progress to become mouth malignancies. Methods: Between 2017 and 2022, 200 patients at a tertiary care facility who were identified with premalignant oral lesions had their medical records retrospectively examined. Information on lesion features, histological results, and demographics was gathered. Statistical analysis was used to determine the prevalence of premalignant oral lesions and the rate at which these lesions turned into oral malignancies, with a significance threshold of P < 0.05. Findings: The research population's mean age was 55 years (SD ± 10), with a 65% male preponderance. The most prevalent premalignant lesions were leukoplakia (45%), erythroplakia (30%), and oral submucous fibrosis (25%). Remarkably, during follow-up, 40% of patients showed development of premalignant lesions into mouth malignancies. Based on statistical analysis, there were significant correlations (P < 0.05) between dysplastic alterations, age, tobacco use, and the development of oral malignancies from premalignant lesions. Conclusion: In conclusion, this study highlights the need of early diagnosis and focused therapies in tertiary care settings by offering important insights into the occurrence and evolution of premalignant oral lesions. The results provide important information that may be used to create screening programs and preventive measures that will lessen the incidence of oral cancer.